Integrated qualitativeness in design by multi-objective optimization and interactive evolutionary computation. - Brintrup, Alexandra Melike; Ramsden, Jeremy J.; Tiwari, Ashutosh (Cranfield University, 2005)
Abstract- The concept of qualitativeness in design is an important one, and needs to be incorporated in the optimization process for a number of reasons outlined in this paper. Interactive Evolutionary Computation and Fuzzy Systems are two of the widely used approaches for handling qualitativeness in design optimization. This paper classifies the types of qualitativeness observed in design optimization, makes the case for their necessity, and proposes a novel framework for handling them, combining the two approaches in an evolutionary multi-objective optimization platform. Two components of the framework are tested using the floor-planning problem, and observations are reported. Future work is defined onthe development of the framework.